2018
DOI: 10.21037/jtd.2017.12.34
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracic surgery for thymoma: long-term follow-up results and prognostic factors—single-center experience of 150 cases

Abstract: VATS was a safe and effective procedure for treatment of thymomas with satisfactory prognosis. MG with thymoma treated by VATS had comparable neurological outcome to that associated with the trans-sternal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Previous articles have reported that WHO classification, Masaoka stage, and R0 resection status may influence the recurrence and long‐term prognosis of thymomas . COX regression analysis in our study indicated that Masaoka stage III + IV, not‐R0 resection, and recurrence were independent risk prognostic factors, but older age seemed to be a protective factor for recurrence, which was similar to the study by Li . The role of postoperative radiotherapy for thymomas remains controversial .…”
Section: Discussionsupporting
confidence: 87%
“…Previous articles have reported that WHO classification, Masaoka stage, and R0 resection status may influence the recurrence and long‐term prognosis of thymomas . COX regression analysis in our study indicated that Masaoka stage III + IV, not‐R0 resection, and recurrence were independent risk prognostic factors, but older age seemed to be a protective factor for recurrence, which was similar to the study by Li . The role of postoperative radiotherapy for thymomas remains controversial .…”
Section: Discussionsupporting
confidence: 87%
“…In addition, this study included 1 case of suspected thymoma without a preoperative manifestation of myasthaenia gravis or signs of invasion in imaging. VATS appears to be feasible and safe for the resection of early-stage thymomas compared to median sternotomy [ 13 , 14 ]. Furthermore, VATS is reliable and safe for resection of large and invasive mediastinal tumours [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that age and Masaoka-Koga stage were prognostic factors for thymomas. 4 Similarly, Mou et al concluded that age, Masaoka-Koga stage, and postoperative radiation were prognostic factors for thymomas; 5 however, Yanagiya et al demonstrated that age and histological type rather than Masaoka-Koga stage were meaningful prognostic factors. 6 To date, large-scale studies on the prognostic factors of thymomas have been limited and the reported associations have not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Several survival predictors for thymomas have been proposed. Li et al reported that age and Masaoka–Koga stage were prognostic factors for thymomas . Similarly, Mou et al concluded that age, Masaoka–Koga stage, and postoperative radiation were prognostic factors for thymomas; however, Yanagiya et al demonstrated that age and histological type rather than Masaoka–Koga stage were meaningful prognostic factors .…”
Section: Introductionmentioning
confidence: 99%